Penyuluhan Komunikasi Non Verbal Pada Himpunan Pramuwisata Indonesia (HPI) Kabupaten Bogor - Imani Satriani; Qoute Nuraini Cahyaningrum (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Tourism in Bogor Regency always has its own charm for tourists. Tourism activities in Bogor close related with tourguide. Himpunan Pramuwisata Indonesia (HPI) Bogor is an organization who cope tour guides in Bogor Districts. Tour guide must have communication ability besides knowledge of tourist destination. Communication divided into verbal and non verbal communication. Verbal communication like oral and written communication. Non verbal communication like facial expression, gesture, dialect, etc. This Non Verbal Communication counseling is a part of community serices activity with title Public Speaking and Non Verbal Communication for Tourist Guide. This activity aims to optimize tour guide’s knowledge about nonverbal communication and to optimize tour guide’s knowledge about nonverbal communication and it impelementations in tourism activities. Methodes of this PKM implementation are lecture method, disscused and feedback collection method. The results of this community service activities including that HPI members become knowledgeable about non verbal communication in general. HPI members also become knowledeable about non verbal communication for tourism activities.